Carpet Characteristics of Eichhornia Crassipes [Mart.] Solms (Water hyacinth) in the Winam Gulf (Lake Victoria, Kenya) - Opande, George T; Otieno, Wagai S; Charles, Onyango J; Musyimi, David M (Journal of Asian Scientific Research, 2017)
The occurrence and spread of the water hyacinth (Eichhornia crassipes [Mart.] Solms), in the Winam gulf has created numerous attributes to the human population that live around the lake, thereby making its control a priority. Navigation within the lake is a major economic activity that has been greatly affected. Before this study, little was known about the characteristics of these weed carpets, and specifically the weight that a healthy inter-connected or entangled carpet can support before it was able to sink or even get submerged. Can a light herbivore or human stranded in the lake walk on a healthy carpet to safety?. In order to better understand these unknown, a study was initiated at five locations (i.e; Dunga beach, Kisumu pier, Kusa, Kobala and Kendu bay) within the lake that appeared to contain healthy dense carpets. Carpet connectivity, mat buoyancy, distribution of mass, biomass density, rhizome length and population density were calculated. Carpet connectivity was determined as the difference in pressure when weights were added on a mesh wire measuring 0.434m2 until the carpet submerged and the pressure on the same carpet that was required to submerge it after a complete disconnection. Standing population density was determined by counting the number of plants found within quadrants measuring 1 m2; while biomass density was determined when oven dried plant materials collected from quadrants measuring 1 m2 was weighed. Plant mass and rhizome length measurements were correlated, while population density was correlated to biomass density. These observations show that water hyacinth distribution in the Winam gulf is seasonal and adopts residence in secluded bays, carpets measuring 0,434m2 in size that have a connectivity of 288.4 Pa (pascals) are able to support a weight of only 12.6 kg, with any additional weight causing them to submerge. Distribution of mass was normal except in locations that are subjected to external factors.